Why I Hit Him: Women's Reasons for Intimate Partner Violence. - Caldwell, Jennifer E; Swan, Suzanne C; Allen, Christopher T; Sullivan, Tami P; Snow, David L (Journal of aggression, maltreatment & trauma, 2009)
This study examines motives for intimate partner violence (IPV) among a community sample of 412 women who used IPV against male partners. A "Motives and Reasons for IPV scale" is proposed, and exploratory factor analyses identified five factors: expression of negative emotions, self-defense, control, jealousy, and tough guise. To our knowledge, the study is the first to investigate the relationship between women's motives for IPV and their perpetration of physical, psychological, and sexual aggression, as well as coercive control, toward partners. Hierarchical regression analyses revealed participants' aggression was driven by complex, multiple motives. All five motives were related to a greater frequency of perpetrating IPV. Treatment programs focusing on women's IPV perpetration should address both defensive and proactive motives.